BIOFORMULATION OF HALOTOLERANT PGPR FOR ENHANCING SALINITY TOLERANCE IN TRITICUM AESTIVUM - Agnihotri, Shivangi; Waoo, Ashwini. A.; Rai, Piyush Kant (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Biofertilizers derived from microorganisms are an environmentally friendly and economical alternative to chemical fertilizers, supporting sustainable agriculture by enhancing crop productivity. Halo-tolerant plant growth-promoting rhizobacteria (PGPR) can significantly improve the growth of plants in saline soils, which are becoming increasingly prevalent due to climate change. This study isolated and characterized nine rhizobacterial strains from the saline soil of Auraiya district, Uttar Pradesh, India. Among them, two of the isolates identified as (HS7) and (HS3), were selected based on their high salinity tolerance and plant growth-promoting properties. These isolates were formulated with talc and charcoal as carrier materials and tested for their efficacy in improving the growth of wheat plants in saline stress. The results demonstrated that both carriers were equally effective, suggesting that talc could be a more environmentally friendly alternative to charcoal. The study concludes that these PGPR strains can mitigate the negative effects of salinity on wheat crops, highlighting their potential as biofertilizers for sustainable agriculture.